O registro do teatro de “pássaros juninos” como patrimônio histórico e cultural imaterial brasileiro - SILVA, Renan Cordeiro da (2023)
The Theather Performance of Pássaros Juninos is a historical cultural expression of the Amazon and brings an artistic rarity like your main characteristic. More than becoming entangled in the “Amazonian imagination”, this scenic expression is the product of important temporal episodes in the north of the country. Based on such data on the preciousness contained in the popular culture of Pássaros Juninos, the present research turns to analyzing the State's obligation to promote the safeguarding of this cultural heritage, through the appropriate legal tools, with emphasis on the Registration of Intangible Cultural Heritages, foreseen from Article 215 of the Constitution of the Federative Republic of Brazil (1988). To this end, the discussion encompasses several concepts, which are indirectly placed as requirements for the protection of cultural heritage, namely the right and heritage, historicity, culturality and immateriality. It is demonstrated, in the study on screen, the congruence between the cultural characteristics present in the Pássaros Juninos and the aspects that determine the consideration of an asset as intangible cultural heritage. Thus, the identification of the aforementioned popular theater as an object of indispensable protection by the Public Power is concluded.